2009
DOI: 10.1002/syn.20666
|View full text |Cite
|
Sign up to set email alerts
|

c‐Fos expression associated with reinstatement of cocaine‐seeking behavior by response‐contingent conditioned cues

Abstract: Summary The capability of cocaine cues to generate craving in cocaine-dependent humans, even after extended abstinence, is modeled in rats using cue reinstatement of extinguished cocaine-seeking behavior. We investigated neural activity associated with incentive motivational effects of cocaine cues using c-fos mRNA and Fos protein expression as markers. Unlike preceding studies, we used response-contingent presentation of discrete cues to elicit cocaine seeking. Rats were first trained to press a lever, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 63 publications
9
77
5
1
Order By: Relevance
“…We therefore suggest that the novel stimuli may have activated similar reinforcement and motivation processes as those involved in conditioned reinforcement-seeking behavior. In support, the Fos expression resulting from novel cue reinforcement was highly similar to that found previously during CS + re-exposure (Kufahl et al, 2009;Neisewander et al, 2000). The latter study also used a no-lever control group and found similar activation, suggesting that our findings are not due to the act of operant responding, but instead likely reflect circuits that have a role in drug motivational processes invoked for expression of cocaine-seeking behavior (Fuchs et al, 2002(Fuchs et al, , 2004(Fuchs et al, , 2006Ito et al, 2004;Kalivas and McFarland, 2003;Kruzich and See, 2001b).…”
Section: Novelty Reinforcementsupporting
confidence: 88%
See 2 more Smart Citations
“…We therefore suggest that the novel stimuli may have activated similar reinforcement and motivation processes as those involved in conditioned reinforcement-seeking behavior. In support, the Fos expression resulting from novel cue reinforcement was highly similar to that found previously during CS + re-exposure (Kufahl et al, 2009;Neisewander et al, 2000). The latter study also used a no-lever control group and found similar activation, suggesting that our findings are not due to the act of operant responding, but instead likely reflect circuits that have a role in drug motivational processes invoked for expression of cocaine-seeking behavior (Fuchs et al, 2002(Fuchs et al, , 2004(Fuchs et al, , 2006Ito et al, 2004;Kalivas and McFarland, 2003;Kruzich and See, 2001b).…”
Section: Novelty Reinforcementsupporting
confidence: 88%
“…In response to cocaine or cocaine-paired cues, Fos is expressed in brain regions commonly associated with reward processing, memory, and drug abuse (Ciccocioppo et al, 2001;Hotsenpiller et al, 2002;Neisewander et al, 2000). More recently, we found that presentation of response-contingent cocaine-paired cues during reinstatement testing induced a widespread pattern of Fos expression throughout the brain, including several prefrontal cortical, limbic, and striatal subregions (Kufahl et al, 2009). Although the association between cue presentation and brain activation appears to rely on previous drug-stimulus pairings (Guo et al, 2008;Miller and Marshall, 2005), little attention has been given to the contribution of novelty on test day.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The NAc, under the influence of dopamine (DA) release from the ventral tegmentum and glutamatergic afferents from the PFC, amygdala, and hippocampus, integrates limbic information related to memory, drive, and motivation with the generation of goal-directed motor behaviors (23). This area is also activated by conditioned cues in rats undergoing a variety of extinction manipulations (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…These findings obtained in NAcc shell MSNs are consistent with adaptations processing information necessary for contextual conditioning and do not argue against similar changes occurring in the NAcc core. Indeed, both changes in c-Fos expression (Kufahl et al, 2009) and in spine morphology (Gipson et al, 2013) have been reported in the NAcc core following the presentation of discrete drug-paired cues.…”
Section: Associative Conditioningmentioning
confidence: 99%